If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 21x + -5 = 3 + 7x Reorder the terms: -5 + 21x = 3 + 7x Solving -5 + 21x = 3 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -5 + 21x + -7x = 3 + 7x + -7x Combine like terms: 21x + -7x = 14x -5 + 14x = 3 + 7x + -7x Combine like terms: 7x + -7x = 0 -5 + 14x = 3 + 0 -5 + 14x = 3 Add '5' to each side of the equation. -5 + 5 + 14x = 3 + 5 Combine like terms: -5 + 5 = 0 0 + 14x = 3 + 5 14x = 3 + 5 Combine like terms: 3 + 5 = 8 14x = 8 Divide each side by '14'. x = 0.5714285714 Simplifying x = 0.5714285714
| x^2+60x+792=0 | | -2(-3x+4)+3x=42 | | -12x^2-2x=4 | | sa+3b=7a | | (3a+5)(4a)= | | 0.2x-4=0.4+4 | | P=20-4q | | 0.30x=0.25x+1 | | 6+12x+36=7x+30+6x | | (2x-7)-(3x+5)=5(x-3) | | f(x)=x^4-9x^2+18 | | 8a=4b-20 | | 6-10x=0 | | 2x+66=5x+9 | | (x+2)*(5-3x)= | | C^2-15c-54=0 | | 4(x+6)-x(x+6)=0 | | lg(2x)=4.5 | | 4(n-3)-3n=1+2 | | cos^2x+5cosx=1 | | 15x-17=22 | | 10+7f=8f | | 2x+18=-3y | | 3*(5*x-7)+2*(2*x+17)=5*(3*x-4)+37 | | (3y-5)(8-y)=0 | | 4(x)=3x-1 | | X^2+x=0.24 | | 3(1)-2(6)=9 | | 5x+1=-16 | | 6(y+2)=-3(6y-1)+6y | | 13X=10X-9 | | Y=-x(x-2) |